Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am scratching my head to figure out a way to separate variables of the following equation:

$$(t+3)(t-2)dx = (t+tx^2)dt$$

Doesn't matter how many times I divide and multiply, I always get $x$ and $t$ on one side. Is there a trick applicable here?!

share|improve this question
9  
$(t+tx^2) = t(1+x^2)$ –  Antonio Vargas May 3 '12 at 23:38

1 Answer 1

up vote 3 down vote accepted

$$ (t+3)(t-2) dx = (t+tx^2)dt \Rightarrow (t+3)(t-2)dx=t(1+x^2) dt \Rightarrow \frac{dx}{1+x^2}=\frac{t}{(t+3)(t-2)} dt $$ I assume you can take it from here.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.